2008
DOI: 10.21273/hortsci.43.3.885
|View full text |Cite
|
Sign up to set email alerts
|

Annual Bloom-time Phosphorus Fertigation Affects Soil Phosphorus, Apple Tree Phosphorus Nutrition, Yield, and Fruit Quality

Abstract: A randomized, complete block, split-plot experimental design with six replicates was established and maintained annually for the first five fruiting seasons (1999 to 2003) in a high-density apple [Malus sylvestris (L) Mill var. domestica (Borkh.) Mansf] orchard on M.9 rootstock planted in Apr. 1998. Main plot treatments involved eight different nutrient regimes, each containing three tree subplots of each of five different cultivars (Ambrosia, Cameo, Fuji, Gala, and Silken). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Eight rows were required for each block with 16 rows required to encompass the six replicate blocks. Two of the fertigation treatments involved the presence or absence of annual P for which results have previously been described (Neilsen et al, 2008). Pertinent to this report was a factorial combination of six fertigation treatments involving two N rates and three N timings.…”
Section: Methodsmentioning
confidence: 97%
“…Eight rows were required for each block with 16 rows required to encompass the six replicate blocks. Two of the fertigation treatments involved the presence or absence of annual P for which results have previously been described (Neilsen et al, 2008). Pertinent to this report was a factorial combination of six fertigation treatments involving two N rates and three N timings.…”
Section: Methodsmentioning
confidence: 97%
“…In contrast, it might be argued that excessive P applications were made during the study. However, the susceptibility of P to precipitation within the soil (Neilsen et al, 1993;O'Neil et al, 1979) and documented benefits of large P applications at bloom (Neilsen et al, 2008) support maintenance of these P application rates. However, reductions in the B and N application rates may have been possible.…”
Section: Resultsmentioning
confidence: 99%
“…Over the two first production cycles, the firmness of ripe fruits presented average values of 1.37 and 1.57 N, respectively ( Figure 4); but also, no evidence of P fertilizer effect, probably due to the absence of this effect on the percentage of dry matter in the fruits. Research evaluating the influence of P fertilizer on the firmness of some fruits also indicated the lack of response to P (Neilsen, Neilsen, & Toivonen, 2008;Medeiros, Andrade, Pereira, Mendonça, & Fonseca, 2014;A. C. Silva et al, 2016).…”
Section: Physicochemical Characterization From Ripe Fruits Of Bananamentioning
confidence: 99%